FE-49 - A NEW TZ=-3/2 DELAYED-PROTON EMITTER - Cerny, J; Cardinal, C; Evans, H; Jackson, K; Jelley, N (1970)
Iron-49 with a half-life of 75±10 msec was produced by the reaction Ca40(C12,3n)Fe49 using 65-MeV carbon ions; beta-delayed protons with an energy of 1.96±0.05 MeV probably originating from the lowest T=32 state in Mn49 were observed. © 1970 The American Physical Society.